Characterization of Glomerular and Tubulointerstitial Proteomes in a Case of Nonsteroidal Anti-Inflammatory Drug–Attributed Acute Kidney Injury: A Clinical Pathologic Molecular Correlation. Issue 3 (30th March 2023) - Parikh, Samir V.; Madhavan, Sethu; Shapiro, John; Knight, Richard; Rosenberg, Avi Z.; Parikh, Chirag R.; Rovin, Brad; Menez, Steven; ,
Abstract : The major goals of the Kidney Precision Medicine Project (KPMPP) are to establish a molecular atlas of the kidney in health and disease and improve our understanding of the molecular drivers of CKD and AKI. In this clinical-pathologic-molecular correlation, we describe the case of a 38-year-old woman without any history of CKD who underwent a research kidney biopsy in the setting of AKI suspected to be due to nonsteroidal anti-inflammatory use after cesarean section delivery. The participant's histopathology was consistent with mild acute tubular injury, without significant interstitial fibrosis or tubular atrophy. This diagnosis was supported by analysis of the glomerular and tubulointerstitial proteomes. The proteomic interrogation revealed a molecular landscape that demonstrated differences in kidney prostaglandin synthesis that may be in response to nonsteroidal anti-inflammatory drugs and signs of intrarenal inflammation and fibrosis that were not evident by histopathology alone.